Pendidikan Ekonomi Kerakyatan dalam Membentuk Jiwa Entrepreneur - Nerys Lourensius; Kiromim Baroroh; Rian Larasati (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Entrepreneurship plays a dominant role in driving the wheels of the economy both on a local, regional and global scale. The aim of this research is to reveal people's economic education in instilling entrepreneurial values ​​through economic education in society. This research uses the literature study method. The research results show that entrepreneurs who are dynamic and committed to success are proven to influence economic growth and prosperity. This businessman who is full of leadership and entrepreneurial spirit will take on the task of leading an economic revolution to improve a more decent standard of living. In society, entrepreneurial values, such as creativity, innovation, careful risk management, perseverance, responsibility and optimism, must always be instilled in the younger generation. Especially through Economic Education. So that the soul and spirit of the younger generation can be more competitive in facing competition in the era of society. The role of Economic Education is very important in shaping the enthusiasm of the younger generation to become active and participatory actors in driving the economic revolution towards positive change.